Illusions of terrorism and counter-terrorism - English, Richard, 1963- (Oxford [England] : Published for the British Academy by Oxford University Press, 2016)
aThe relationship between non-state terrorism and state counter-terrorism continues to shape world politics. Leading scholars analyse this relationship, examining post-9/11 counter-terrorism, the evolution of al-Qaida, challenges to Western counter-terrorism, and why terrorist campaigns sometimes endure and sometimes end.
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Access type: Perpetual access
Includes bibliographical references and index.
ARC, PPDM.
Mode of access: Internet
Keywords: Terrorism; Terrorism -- Prevention; Electronic books